UPAYA MENCAPAI SDGs POIN KEENAM (AIR BERSIH DAN SANITASI LAYAK): PROGRAM CITARUM HARUM 2018 – 2022 DI KABUPATEN BANDUNG - Akbar, Taufan Herdansyah; Dwiyanto, Yoga (Universitas Jenderal Ahmad Yani, 2024)
Countries around the world have issued the Sustainable Development Goals (SDGs) for the period 2015-2030, inviting all communities worldwide to protect the earth through 17 main goals and 169 targets for sustainable development. The sixth point of the SDGs focuses on the issue of